An analysis of fast-response pressure probes dynamics for ORC power systems. (September 2017) - Molesini, P.; Gori, G.; Guardone, A.
Abstract: The dynamic response of line-cavity systems in ideal and non-ideal compressible-fluid conditions is investigated numerically using the SU2 open-source suite for multi-physics simulations. The response of the system is studied for small but finite pressure perturbations, to predict the behaviour of fast-response pressure probes in turbomachinery for gas and ORC power systems. The probe step-response is found to present significant damping due to non-linear wave propagation. Non-idealities in the close proximity of the liquid-vapour curve increase the signal damping due to non-monotone variations of the speed of sound. A simplified approach is proposed to predict the probe dynamic characteristics in ideal regime. The estimation of the probe dynamics in non-ideal regime is found to be very critical and to strongly depend on the thermodynamic state of the fluid. The present results provides a guideline for the design of fast-response pressure probes to be used e.g. past the rotor stage of ORC turbine vanes.